Ants can play prisoner's dilemma - Tekol, Y; Acan, A (IEEE, 2003)
An Ant Colony Optimization approach towards the development of robust game strategies for iterated prisoner's dilemma (IPD) is presented. It is demonstrated that, ants can play IPD and, in spite of comparably longer running times, provide game strategies of better quality than the Genetic Algorithms. The success of the developed strategies, compared to the ones developed using Genetic Algorithms are illustrated by experimental evaluations.
Congress on Evolutionary Computation (CEC) -- DEC 08-12, 2003 -- Canberra, AUSTRALIA
Keywords: Optimization; Cooperation; Colony